A Comparative analysis of factors influencing strategy implementation : Differences between large companies vs. SME´s and micro-companies - Pöntinen, Elina Matilda (My University, 2025)
Strategy implementation refers to the process through which planned strategies are executed in practice (Heide et al., 2002; Weiser et al., 2020) and is regarded as the most challenging phase of strategic management (Ivancic, 2016; Zaidi et al., 2018), with studies estimating that up to 90% of strategies fail during implementation (Raps, 2004; Cater & Pucko, 2010). Although research on strategic planning is extensive, the execution phase remains underexplored (Tawse & Tabesh, 2021; de Oliveira et al., 2019). Moreover, existing studies focus primarily on large firms, offering limited insight into smaller enterprises (Kelliher & Reinl, 2009; Kearney et al., 2019). The purpose of this thesis is to examine how the practices and factors influencing strategy implementation differ between large and smaller companies. The theoretical framework examines the factors that could hinder or, conversely, facilitate the effective execution of the strategy. These include factors such as clarity and precision in strategic foundations and leadership and management capabilities, as well as other significant factors that influence the implementation process. The research focuses on two large, two medium, three small-sized companies and a micro company. Data is collected through semi-structured interviews, which allows a detailed comparison of practices and challenges related to strategy implementation between the organizations of different sizes. The findings show how factors influencing strategy implementation differ between large and smaller companies. Large firms typically rely on formal structures, clear strategic foundations, and distributed leadership. In smaller firms, implementation is more informal and dependent on individual leaders, often leading to fragmented practices. Resource allocation was considered important across all firm sizes, but only large companies had the capacity to manage it systematically. Small firms particularly struggled with limited leadership and management capabilities. Leadership structures were often underdeveloped, and responsibilities concentrated in the hands of founders. A critical issue discovered was the lack of consensus and commitment between owners, which significantly hindered implementation and, in some cases, led to critical organizational dysfunction. This study highlights significant internal variation within the SME category and shows that size alone does not determine implementation practices. The taxonomy analysis based on Šilenskytė and Smale (2021) reinforces the finding that organizational characteristics, not just size, shape strategic behaviour. The results also challenge the analytical validity of treating size-based categories such as SMEs as homogeneous, suggesting a need for more nuanced segmentation when analysing strategy implementation in different organizational contexts.

Strategian toimeenpanolla tarkoitetaan prosessia, jossa suunnitellut strategiat viedään käytäntöön (Heide et al., 2002; Weiser et al., 2020), ja sitä pidetään strategisen johtamisen haastavimpana vaiheena (Ivancic, 2016; Zaidi et al., 2018). Tutkimusten mukaan jopa 90 % strategioista epäonnistuu nimenomaan toimeenpanovaiheessa (Raps, 2004; Cater & Pucko, 2010). Vaikka strategista suunnittelua on tutkittu laajasti, toimeenpanoon liittyvä tutkimus on edelleen vähäisempää (Tawse & Tabesh, 2021; de Oliveira et al., 2019). Lisäksi olemassa oleva tutkimus keskittyy pääasiassa suuriin yrityksiin, ja tarjoaa vain vähän tietoa pienemmistä organisaatioista (Kelliher & Reinl, 2009; Kearney et al., 2019). Tämän opinnäytetyön tarkoituksena on tarkastella, miten strategian toimeenpanokäytännöt ja niihin vaikuttavat tekijät eroavat suurten ja pienempien yritysten välillä. Teoreettinen viitekehys tarkastelee tekijöitä, jotka voivat joko estää tai edistää strategian tehokasta toteuttamista. Tutkimuksessa tarkastellaan kahta suurta, kahta keskisuurta, kolmea pientä yritystä ja yhtä mikroyritystä. Aineisto kerättiin puolistrukturoiduin haastatteluin, mikä mahdollistaa yksityiskohtaisen vertailun eri kokoisten organisaatioiden toimeenpanokäytännöistä ja haasteista. Tulokset osoittavat, että strategian toimeenpanoon vaikuttavat tekijät eroavat merkittävästi suurten ja pienempien yritysten välillä. Suuryritykset nojaavat tyypillisesti muodollisiin rakenteisiin, selkään strategiaan sekä hajautettuun johtamiseen. Pienemmissä yrityksissä strategia ja sen toimeenpano on usein epämuodollista ja yksittäisten henkilöiden varassa, mikä johtaa hajanaisiin käytäntöihin. Resurssien kohdentaminen koettiin tärkeäksi kaikissa kokoluokissa, mutta vain suuret yritykset pystyivät hallitsemaan sitä järjestelmällisesti. Pienyritykset kamppailivat erityisesti johtamiseen liittyvien haasteiden kanssa. Johtamisrakenteet olivat usein kehittymättömiä ja vastuut keskittyivät perustajille. Erityisen kriittinen havainto oli omistajien välisen yhteisymmärryksen ja sitoutumisen puute, joka vaikeutti toimeenpanoa merkittävästi ja johti joissakin tapauksissa vakaviin häiriöihin organisaatiossa. Tutkimus osoittaa, että SME-luokan sisäinen vaihtelu on merkittävää, ja että pelkkä yrityksen koko ei määritä strategian toimeenpanokäytäntöjä. Šilenskytėn ja Smalen (2021, p.515) taksonomiaan perustuva analyysi vahvistaa havainnon, jonka mukaan strategista käyttäytymistä muovaavat ensisijaisesti organisaation ominaispiirteet, eivät pelkästään koko. Tulokset haastavat kokoluokkaan perustuvien luokitusten, kuten SME-kategorian, analyyttisen pätevyyden ja viittaavat siihen, että strategian toimeenpanoa tulisi tarkastella tarkemmin organisaatioiden ominaispiirteiden perusteella.
Keywords: strategic planning; execution (implementation); fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development